Bad monkey (Alfred A. Knopf, Findaway World, LLC, 2013)
Anticipating his retirement from the Key West Police, Andrew Yancy tackles a murder case involving a human arm in his freezer, an investigation that pits him against a twitchy widow, a clueless real estate developer and a voodoo witch with a string of hapless lovers.

Cross kill (Book Shots, ,, 2016)
Killer Gary Soneji has been dead for over ten years. Alex Cross watched him die. But today, Cross saw him gun down his partner. Is Soneji alive, a ghost, or something even more sinister?

The widowmaker: a novel (Black Harbor, 2,, 2022)
"A wealthy family shrouded in scandal; a detective tasked with solving an impossible cold case; and a woman with a dark past collide in Hannah Morrissey's stunning new Black Harbor mystery, The Widowmaker. Ever since business mogul Clive Reynolds disappeared twenty years ago, the name "Reynolds" has become synonymous with "murder" and "mystery." And now, lured by a cryptic note, down-on-her-luck photographer Morgan Mori returns home to Black Harbor and into the web of their family secrets and double lives. The same night she photographs the Reynolds holiday get-together, Morgan becomes witness to a homicide of a cop that triggers the discovery of a long-buried clue. This could finally be the thing to crack open the chilling cold case, and Investigator Ryan Hudson has a chance to prove himself as lead detective. If only he could stop letting his need to solve his partner's recent murder distract him. But as Morgan exposes her own dark demons, could her sordid history be the key to unlocking more than one mystery?"--

The Last Mile (Amos Decker, 2,, 2016)
Melvin Mars awaits his fate on Death Row. He was one of America's most promising football stars until, aged twenty-years-old, he was arrested and convicted for the murder of his parents just as he was due to begin a very lucrative contract with the NFL. When Amos Decker, newly appointed special agent with the FBI, hears the news that Melvin was saved in the final seconds before his execution because someone has confessed to the killings, he persuades his boss to allow him to carry out an investigation into the Mars murders.

Killer: an Alex Delaware novel (Alex Delaware, 29,, 2014)
"Well-used to elevated emotions, psychologist Alex Delaware shrugs off a joking death threat from beautiful Beverly Hills physician Constance Sykes, whose attempt to secure legal custody of her baby niece is thwarted by Alex's forthright report to the court. Alex plays down the threat until LAPD's Milo Sturgis rushes to his side with the shocking word on the street that a hit's been taken out on him. But while Alex may be in grave danger, it won't be from the Beverly Hills doctor, for Connie's soon discovered brutally slain. When her sister Cherie and the baby disappear, apparently on the run, Alex's search for answers lead him to aged rockers, charming homeboys and even Machiavellian judges. As the darkest of secrets are peeled away, and a cruel system churns through family lives, Alex seeks to stop a vicious killer and save a child from a life of nightmares ... or worse"--

The New Iberia blues (A Dave Robicheaux novel, 22,, 2019)
Detective Dave Robicheaux's world isn't filled with too many happy stories, but Desmond Cormier's rags-to-riches tale is certainly one of them. Robicheaux first met Cormier on the streets of New Orleans, when the young, undersized boy had foolish dreams of becoming a Hollywood director. Twenty-five years later, when Robicheaux knocks on Cormier's door, it isn't to congratulate him on his Golden Globe and Academy Award nominations. Robicheaux has discovered the body of a young woman who's been crucified, wearing only a small chain on her ankle. She disappeared near Cormier's Cyrpemort Point estate, and Robicheaux, along with young deputy, Sean McClain, are looking for answers. Neither Cormier nor his enigmatic actor friend Antoine Butterworth are saying much, but Robicheaux knows better.

Dream town (Aloysius Archer, 3,, 2022)
It's the eve of 1953, and Aloysius Archer is in Los Angeles to ring in the New Year with an old friend, aspiring actress Liberty Callahan, when their evening is interrupted by an acquaintance of Callahan's: Eleanor Lamb, a screenwriter in dire straits. After a series of increasingly chilling events--mysterious phone calls, the same blue car loitering outside her house, and a bloddy knife left in her sink--Eleanor fears that her life is in danger, and she wants to hire Archer to look into the matter. Archer suspects that Eleanor knows more than she's saying, but before he can officially take on her case, a dead body turns up inside of Eleanor's home...and Eleanor herself disappears. Missing client or not, Archer is dead set on finding both the murderer and Eleanor. With the help of Callahan and his partner Willie Dash, he launches an investigation that will take him from mobridden Las Vegas to the glamorous world of Hollywood to the darkest corners of Los Angeles--a city in which beautiful faces are attached to cutthroat schemers, where the cops can be more corrupt than the criminals...and where the powerful people responsible for his client's disappearance will kill without a moment's hesitation if they catch Archer on their trail.

A World of Curiosities (Three Pines mystery, 18,, 2022)
"Chief Inspector Armand Gamache returns in the eighteenth book in #1 New York Times bestseller Louise Penny's beloved series. It's spring and Three Pines is reemerging after the harsh winter. But not everything buried should come alive again. Not everything lying dormant should reemerge. But something has. As the villagers prepare for a special celebration, Armand Gamache and Jean-Guy Beauvoir find themselves increasingly worried. A young man and woman have reappeared in the Sûreté du Québec investigators' lives after many years. The two were young children when their troubled mother was murdered, leaving them damaged, shattered. Now they've arrived in the village of Three Pines. But to what end? Gamache and Beauvoir's memories of that tragic case, the one that first brought them together, come rushing back. Did their mother's murder hurt them beyond repair? Have those terrible wounds, buried for decades, festered and are now about to erupt? As Chief Inspector Gamache works to uncover answers, his alarm grows when a letter written by a long dead stone mason is discovered. In it the man describes his terror when bricking up an attic room somewhere in the village. Every word of the 150-year-old letter is filled with dread. When the room is found, the villagers decide to open it up. As the bricks are removed, Gamache, Beauvoir and the villagers discover a world of curiosities. But the head of homicide soon realizes there's more in that room than meets the eye. There are puzzles within puzzles, and hidden messages warning of mayhem and revenge. In unsealing that room, an old enemy is released into their world. Into their lives. And into the very heart of Armand Gamache's home"--